2021
DOI: 10.3389/fmicb.2021.758161
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus plantarum Lipoteichoic Acids Possess Strain-Specific Regulatory Effects on the Biofilm Formation of Dental Pathogenic Bacteria

Abstract: Bacterial biofilm residing in the oral cavity is closely related to the initiation and persistence of various dental diseases. Previously, we reported the anti-biofilm activity of Lactobacillus plantarum lipoteichoic acid (Lp.LTA) on a representative dental cariogenic pathogen, Streptococcus mutans. Since LTA structure varies in a bacterial strain-specific manner, LTAs from various L. plantarum strains may have differential anti-biofilm activity due to their distinct molecular structures. In the present study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Lactobacilli adhesins can cause significant adhesion to the vaginal wall. The strong adhesion of lactobacilli to the vaginal epithelium results in exclusion and rejection of harmful pathogens ( Lee et al., 2021 ; Kawahara et al., 2022 ). Lactobacilli also exhibit immunomodulatory effects by increasing monocytes and macrophages which play a crucial role in the innate immune response via activation of Toll-like receptors (TLR) and the generation of cytokines ( Mitchell et al., 2021 ).…”
Section: Lactobacilli In the Vagina And Their Crucial Functionmentioning
confidence: 99%
“…Lactobacilli adhesins can cause significant adhesion to the vaginal wall. The strong adhesion of lactobacilli to the vaginal epithelium results in exclusion and rejection of harmful pathogens ( Lee et al., 2021 ; Kawahara et al., 2022 ). Lactobacilli also exhibit immunomodulatory effects by increasing monocytes and macrophages which play a crucial role in the innate immune response via activation of Toll-like receptors (TLR) and the generation of cytokines ( Mitchell et al., 2021 ).…”
Section: Lactobacilli In the Vagina And Their Crucial Functionmentioning
confidence: 99%
“…The LTA structure varies among different bacterial species [ 51 ]. LTAs from various L. plantarum strains also have different effects on anti-biofilm for dental pathogenic bacteria [ 52 ]. Our previous study observed that GMNL-653 uniquely expresses six genes involved in cell wall/membrane/envelop biogenesis compared with the other two L. paracasei strains (GMNL-855 and BCRC 16100).…”
Section: Discussionmentioning
confidence: 99%
“…have shown to inhibit the growth of Streptococcus sp. ( Wasfi et al, 2018 ; Lee et al, 2021 ; Kim et al, 2022 ). Lactobacillus sp.…”
Section: Discussionmentioning
confidence: 99%